Thiourea Derivatives as Estrogen Receptor Alpha Inhibitors for Breast Cancer Therapy: An In Silico Evaluation with ADMET Prediction and Molecular Docking - Puspaweni, Hestining; Purwanto, Bambang Tri; Widiandani, Tri; Siswodihardjo, Siswandono; Muchlisin, M. Artabah (Borneo Journal of Pharmacy, 2024)
Breast cancer remains a significant public health concern, necessitating the discovery of novel therapeutic agents. This study investigates the potential of thiourea derivatives, specifically HU, HTMX, and BMPTU compounds, as estrogen receptor alpha (ERα) inhibitors using computational approaches. Drug-likeness assessments using Lipinski's Ro5 confirmed the oral bioavailability of all compounds. Additionally, ADMET analysis indicated favorable pharmacokinetic properties, with minimal metabolic interactions and acceptable safety profiles, except for BMPTU2, which showed potential hepatotoxicity. Molecular docking simulations revealed strong binding affinities between BMPTU derivatives, particularly BMPTU2, BMPTU3, and BMPTU4, and key ERα residues. These interactions suggest their potential as ERα modulators, warranting further in silico and experimental validation. In conclusion, the findings highlight the potential of BMPTU derivatives, especially BMPTU2, BMPTU3, and BMPTU4, as promising lead compounds for developing novel ERα-targeted breast cancer therapies. Further optimization and validation are crucial to fully elucidate their therapeutic potential.